Western Australian food security project - Maycock Bruce; Brown Graham; McManus Alexandra (BMC, 2007)
Abstract Background The aim of the Western Australian (WA) Food Security Project was to conduct a preliminary investigation into issues relating to food security in one region within the Perth metropolitan area in Western Australia. The first phase of the project involved a food audit in one lower income area that was typical of the region, to identify the range, variety and availability of foods in the region. Methods A comprehensive food audit survey was provided to all food outlet owners/operators in one lower socio-economic region within the City of Mandurah (n = 132 outlets). The purpose of the survey was to investigate the range, variety and availability of foods in the Mandurah region as well as examining specific in-store characteristics such as the types of clientele and in-store promotions offered. Surveys were competed for 99 outlets (response rate = 75%). Results The range of foods available were predominantly pre-prepared with more than half of the outlets pre-preparing the majority of their food. Sandwiches and rolls were the most popular items sold in the outlets surveyed (n = 51 outlets) followed by pastries such as pies, sausage rolls and pasties (n = 33 outlets). Outlets considered their healthiest food options were sandwiches or rolls (n = 51 outlets), salads (n- = 50 outlets), fruit and vegetables (n = 40 outlets), seafood (n = 27 outlets), meats such as chicken (n = 26 outlets and hot foods such as curries, soups or quiches (n = 23 outlets). The majority of outlets surveyed considered pre-prepared food including sandwiches, rolls and salads, as healthy food options regardless of the content of the filling or dressings used. Few outlets (n = 28%) offered a choice of bread type other than white or wholemeal. High fat pastries and dressings were popular client choices (n = 77%) as were carbonated drinks (n = 88%) and flavoured milks (n = 46%). Conclusion These findings clearly indicate the need for further investigation of the impact of access to quality, healthy foods at reasonable cost (food security) on public health, particularly in lower socio-economic areas.